2017
DOI: 10.1159/000465528
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Variability in Obstructive Sleep Apnoea: Data from 4 Randomised Controlled CPAP Withdrawal Trials

Abstract: Background: Increased daytime blood pressure variability (BPV) is associated with cardiovascular risk. Preliminary data suggest that obstructive sleep apnoea (OSA) might contribute to increased daytime BPV. Objective: The aim of this study was to evaluate the effect of continuous positive airway pressure (CPAP) therapy withdrawal on daytime BPV. Methods: A total of 183 patients previously diagnosed with OSA and treated with CPAP were randomised to either continue or withdraw from CPAP within 4 trials. Office m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
4
10
0
Order By: Relevance
“…This observation is in keeping with the results of several previous studies, 16,17 and may have straightforward interpretations.…”
Section: Ambulatory Recording Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is in keeping with the results of several previous studies, 16,17 and may have straightforward interpretations.…”
Section: Ambulatory Recording Modelsupporting
confidence: 92%
“…ODI was assessed by overnight finger pulse oximetry in 2342 participants on the day of ambulatory BP monitoring, and calculated as the number of desaturation episodes per sleeping hour. Both BP and pulse rate increased significantly (P ≤ .006) from normal (< 5 events/h) to mildly (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), moderately (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and severely (≥ 30 events/h) elevated ODI. The association for BP was substantially attenuated by accounting for pulse rate (partial r² from .003-.012 to .002-.006).…”
Section: O R I G I N a L P A P E Rmentioning
confidence: 98%
“… 86 Finally, a group of investigations evaluated BP variability with office or home BP measurements, and found some effect of CPAP treatment on waking systolic BP variability. 92 , 124 In summary, CPAP treatment acutely decreases nocturnal very short-term BP variability. A few weeks of CPAP treatment may convert a nondipping into a dipping 24-hour BP profile in some patients and cause some decrease in diurnal BP variability, but more data are necessary to explore these aspects better.…”
Section: Bp Variability In Osamentioning
confidence: 91%
“…No effect on morning-to-morning BP was reported during CPAP withdrawal for 2 weeks, which suggested that OSA does not significantly influence midterm BP variability. 92 …”
Section: Bp Variability In Osamentioning
confidence: 99%
“…In addition to systemic hypertension, blood pressure variability has been suggested as an independent cardiovascular risk factor (16). However, within the CPAP withdrawal trials, randomising 183 patients to either continue therapeutic CPAP or to withdraw it, there was only a negligible increase in within-visit variability in systolic office blood pressure, whereas there was no effect of withdrawing CPAP on other short-term blood pressure variability indices (within-visit), or on intermediateterm blood pressure variability indices (visit-to-visit, day-to-day) (17). The hypothesis that OSA contributes to vascular damage via elevated daytime blood pressure variability could not be supported.…”
Section: Physiological Effects Of Cpap Withdrawalmentioning
confidence: 99%